Evaluasi Efektivitas Tata Kelola Taman Bacaan Masyarakat dalam Meningkatkan Literasi dan Kualitas Pembelajaran Nonformal melalui Model CIPP - Syarifudin Yunus (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to evaluate the effectiveness of Community Reading Park (TBM) governance in improving literacy and the quality of non-formal learning using a mixed-methods approach, specifically the CIPP evaluation model (Context, Input, Process, Product). The research involved a sample of 12 TBM managers and officials from the Bogor Regency Education and Culture Office. The instruments used included questionnaires, interviews, observations, document reviews, and focus group discussions. The findings indicated that the effectiveness of TBM governance in enhancing literacy and the quality of non-formal learning is largely determined by the integration of context, input, process, and product aspects within the CIPP model. TBMs play a positive role in promoting community literacy, particularly by providing access to reading materials and learning spaces. However, limitations in the input aspects were identified, such as the quality and quantity of book collections, human resources, and financial support. The average effectiveness of TBM governance using the CIPP model was 3.56, which is classified as effective, contributing to improved literacy and non-formal learning quality. However, TBMs are not yet supported by adequate human resources, with 70% of TBMs having fewer than 10 volunteers. TBMs have great potential to become community-based literacy centers if managed more systematically and oriented toward community needs. Strengthening is required in areas such as planning, capacity building for managers, development of relevant collections, and support from various stakeholders to improve TBM management effectiveness.